CXCL4 downregulates the atheroprotective hemoglobin receptor CD163 in human macrophages - Gleißner, Christian A.; Shaked, Iftach; Erbel, Christian; Böckler, Dittmar; Katus, Hugo; Ley, Klaus (Journal of banking and finance, 2010)
RATIONALE: CXCL4 is a platelet-derived chemokine that promotes macrophage differentiation from monocytes. Deletion of the PF4 gene that encodes CXCL4 reduces atherosclerotic lesions in ApoE(-/-) mice. - OBJECTIVE: We sought to study effects of CXCL4 on macrophage differentiation with possible relevance for atherogenesis. - METHODS AND RESULTS: Flow cytometry for expression of surface markers in macrophage colony-stimulating factor (M-CSF)- and CXCL4-induced macrophages demonstrated virtually complete absence of the hemoglobin scavenger receptor CD163 in CXCL4-induced macrophages. mRNA for CD163 was downregulated as early as 2 hours after CXCL4. CD163 protein reached a minimum after 3 days, which was not reversed by treatment of cells with M-CSF. The CXCL4 effect was entirely neutralized by heparin, which bound CXCL4 and prevented CXCL4 surface binding to monocytes. Pretreatment of cells with chlorate, which inhibits glycosaminoglycan synthesis, strongly inhibited CXCL4-dependent downregulation of CD163. Similar to recombinant CXCL4, releasate from human platelets also reduced CD163 expression. CXCL4-differentiated macrophages were unable to upregulate the atheroprotective enzyme heme oxygenase-1 at the RNA and protein level in response to hemoglobin-haptoglobin complexes. Immunofluorescence of human atherosclerotic plaques demonstrated presence of both CD68+CD163+ and CD68+CD163- macrophages. PF4 and CD163 gene expression within human atherosclerotic lesions were inversely correlated, supporting the in vivo relevance of CXCL4-induced downregulation of CD163. - CONCLUSIONS: CXCL4 may promote atherogenesis by suppressing CD163 in macrophages, which are then unable to upregulate the atheroprotective enzyme heme oxygenase-1 in response to hemoglobin.